2020
DOI: 10.1111/nmo.13924
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution manometry in the upright position could improve the manometric evaluation of morbidly obese patients with esophagogastric junction outflow obstruction

Abstract: Background: Esophagogastric junction outflow obstruction (EGJOO) detected by manometry in the supine position is prevalent in patients with morbid obesity, but not all EGJOOs are clinically significant. We investigated whether including upright swallows during high-resolution manometry (HRM) could help identify non-clinically significant EGJOO in patients with morbid obesity. Methods: We performed a retrospective study of consecutive morbidly obese patients diagnosed with EGJOO by HRM from July 2012 through Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It can be concluded that esophageal manometry in the upright position could reduce EGJOO overdiagnosis in patients with morbid obesity. Looking more critically at the study it could be concluded that the finding of EGJOO can probably entirely be ignored in the morbidly obese, even when still present in the upright position 19 …”
Section: Clinically Relevant Egjoomentioning
confidence: 99%
See 4 more Smart Citations
“…It can be concluded that esophageal manometry in the upright position could reduce EGJOO overdiagnosis in patients with morbid obesity. Looking more critically at the study it could be concluded that the finding of EGJOO can probably entirely be ignored in the morbidly obese, even when still present in the upright position 19 …”
Section: Clinically Relevant Egjoomentioning
confidence: 99%
“…It can also be erroneously elevated due to various pressure measurement artifacts 5,29‐32 . Given these factors, it is not surprising that findings of elevated IRP are not always reproducible on repeat HRM testing, 4,20 or after postural changes 12,13,19 . Some patients with elevated IRP do not present with obstructive symptoms or radiographic evidence of impaired esophageal bolus transport 17 …”
Section: Egjoo Classificationmentioning
confidence: 99%
See 3 more Smart Citations